Level of non-adherence and associated factors among children on antiretroviral therapy in public hospitals of South Wollo Zone, Northeast Ethiopia - Wondifraw, Endalk Birrie; Belege Getaneh, Fekadeselassie; Amare, Muluken; Mihret, Setegn; Biset, Gebeyaw; Desu Tefera, Birhanu; Zeleke, Mulusew; Ahmed, Fuad; Chanie, Ermias Sisay (Frontiers in Public Health, 2025)
BackgroundPoor adherence to antiretroviral therapy (ART) occurs when an individual with Human Immune deficiency Virus does not follow the prescribed treatment regimen correctly. This includes missing doses, not taking medication as scheduled, taking medication inconsistently or irregularly, and failing to adhere to specific instructions. The lack of adherence to antiretroviral therapy (ART) among children is a noteworthy issue that necessitates attention. The study aims to determine the level of non-adherence to antiretroviral therapy (ART) and its associated factors in children receiving ART in public hospitals in the South Wollo Zone.MethodsA multi-center cross-sectional study was conducted among children receiving antiretroviral therapy at South Wollo Zone public hospitals. A single population proportion formula was used to determine the required sample size. A computer-generated simple random sampling method was employed to select the participants. The tools used to assess adherence for all participants were viral load monitoring, Self-reporting, Pill counts, and Pharmacy refill records. Data were collected through face-to-face interviews, and reviewing patients’ documents using a structured checklist. The data were entered into Epi Data version 4.1 and analyzed using STATA 17. Binary logistic regression was employed to evaluate the relationship between the factors and the outcome variable. Variables were considered significant if the p-value was less than 0.05.ResultOf 291 participants, 286 were involved in the study, making the response rate 98.3%. The mean age of the participants was 7.8 years old (±3.64 SD), and half of the 146 children (51%) were male. The overall proportion of ART non-adherence was 24.1% (95% CI: 19.2–29.0%). Positive TB status (Adjusted odd ratio (AOR) = 4.10, 95% CI: 1.90–8.88), diagnostic status not disclosed (AOR = 2.69, 95% CI: 1.43–5.00), and poor caregiver knowledge (AOR = 2.18, 95% CI: 1.04–4.56) were significantly associated with poor adherence.ConclusionAccording to the current study, the level of non-adherence to antiretroviral therapy remains high compared to the targets set by the United Nations Joint Program on HIV/AIDS (UNAIDS) Project 95-95-95. TB co-infection, undisclosed diagnostic status, and poor caregiver knowledge were found to be significantly associated with non-adherence. Before and throughout ART, healthcare providers should provide intense and ongoing counseling to children and their caregivers.